Levantamento e avaliação de critérios para a ampliação de escala da produção de biossurfactantes utilizando melaço como substrato - Bezerra, Márcio Silva (2006)
Biosurfactants are amphiphilic molecules synthesized by microorganisms such as bacteria, yeast or filamented fungi cultivated in various carbon sources among sucrose and hydrocarbons. These molecules are composed by a hydrophilic and hydrophobic part. They operate mostly at interfaces of fluids of different polarities. Because of this characteristic, they are potentially employed in numerous industries, such as the textile, medical, cosmetics, food and mainly in the petrochemical ones. Therefore industry has interest in developing new biosurfactant production processes in high scale, in order to become them economically competitive when compared to synthetic biosurfactants. This work aims to evaluate the biosurfactant production applying a non-conventional substrate sugar cane molasses proceeding from the sugar industry thus reducing the production costs. The strain identified as AP029/GLIIA, isolated from oil wells in Rio Grande do Norte state and used in these experiments belongs to the culture collection of Antibiotics Department of UFPE. The fermentation were carried out using different conditions according to a factorial planning 24 with duplicate at center point, in which the studied factors were molasse concentration, nitrate concentration, agitation and aeration ratio. The experiments were performed in a shaker at 38ºC of temperature. Samples were withdrawn in regular periods of time of up to 72 hours of fermentation in order to analyze substrate consumption, cellular concentration, superficial tension, critical micelle dilution (CMD-1 e CMD-2) as well as extracelullar protein production. The results showed a production of 3,480 g/L of biomass, a reduction of 41% on superficial tension, 67% of substrate consumption and 0,2805 g/L of extracellular protein